PEACE JOURNALISM (Konsep, Realitas, dan Perspektif Islam) - Nurdin, Ali (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2016)
The news balance is the key factor in the implementation of the Peace Journalism. This term became popular discourse to be applied in the writing of news media and a concept that was born out of the reality of the news circuit that generates a negative effect on media audiences. On the other hand, the news media tends to drift to war journalism (war journalism) that the message is more provocative “stirred” niche audiences heart. The provocative character of the news media is of course intended as well as the business area of media propaganda. Media can be likened to a double-edged knife that had the same sharpness in their respective functions. Media in reporting tends to fall asleep with a frame and forget about aspects of media business news politeness as the balance of news that can give peace to the audience. In this case, the concept of Islam in the news is to be consistent with the concept of reason and benefit of the people. The context of news in the media must have the honesty, accuracy, fairness (impartial one) and accountable